EVALUATION OF SUPPLEMENTING HERBAL PRODUCT TO SOWS FOR IMPROVING LITTER WEIGHT AND REDUCING PIGLET MORTALITY - Chakravarthi, M. Kalyana; Ravikanth, K.; ., Adarsh; Reothia, Ankush (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To examine the impact of the herbal product in improving litter weight, reducing piglet mortality and increasing milk production in sows. Methods: 20 sows which were in their late gestation period were randomly divided into two groups (n=10). Group T0 sows served as no treatment control group, and T1 group sows were supplemented with herbal galactagogue premix, Payapro (M/S Ayurvet Ltd., Baddi) administered for 5 d prior to farrowing and & 10 d post farrowing. Results: The analyses of result revealed that the postpartum milk yield (Approximately for 2 mo) was found to be increased in Payapro supplemented group (166 liters) in comparison to control group (103.5 liters). A significant reduction in mortality in Payapro supplemented group was evident at the time of weaning. Mean piglet weight was improved in the treatment group by 38.8%. Average litter size was also more in Payapro supplemented group (8.6) than the control group (7.7). Conclusion: Payapro premix can enhance the sow productivity in terms of milk production and number of. pigs produced per litter. Keywords: Galactogogue, Mean piglet weight, Average mortality Â